Applying hybridity: rhythms of the Hajj, Tumblr, and Snowden (Glocalism: Journal of Culture, Politics and Innovation, 2013)
Hybridity has long been a contested term, critiqued as elitist and contradictory. This paper begins by arguing that hybridity has been debated too often and applied too seldom. It takes the premise that hybridity is an everyday fact of life and accordingly it should be articulated in academic works as a mode of analysis. In acknowledging works that call for the utilization of hybridity’s analytical potential this work applies hybridity to the analysis of three disparate topics, the modern pilgrimage to Mecca or hajj, the social networking and blogging platform Tumblr, and the Edward Snowden affair. Hybridity is contrasted with Lefebvre’s rhythmanalysis and applied as a conjoined conceptual focus on these issues. In each scenario a variety of hybrid connections are presented and situated in Bauman’s liquid modernity. These representations of hybridity highlight the manifold dimensions of the concept itself, that it can be superficial, political, celebrated, progressive, and mundane. Rather than dismiss the conceptual complexities of hybridity this paper calls for a harnessing of the broad scope of inference that hybridity presents in application. Working with hybridity thus provides a way to link topics and work organically between multiple disciplines.
Keywords: hybridity; haji; Tumblr; Snowden affair; liquid modernity